MO088CLINICOPATHOLOGICAL FEATURES OF THROMBOTIC MICROANGIOPATHY. (29th May 2021) - Menezes, Maria Do Mar; Soares, Elsa; Viana, Helena; Góis, Mário; Nolasco, Fernando
Abstract: Background and Aims: TMA is a rare and severe endothelial lesion with thrombus formation and vascular occlusion with organ damage. It can be a complication of several clinical conditions. The aim of this study was to characterize clinical and pathological findings of patients with confirmed kidney TMA. Method: We performed a retrospective observational descriptive study that analyzed all patients with TMA diagnosed by kidney biopsy, in two hospital centers, from January 2015 until December 2020. Clinical, laboratorial, pathologic characteristics were analyzed as also therapeutic performed and kidney and patient outcomes. Results: Our sample had 14 patients, the majority female (n=11, 78%) with a mean age of 45±10 years-old and 12 (80%) were Caucasian. Six (40%) had past medical history of HTA, 2 (13%) had Multiple Myeloma, 4 (26%) transplant (3 kidney, 1 lung) and none had positive viral serology's. Prodromal symptoms included diarrhea in 2 (13%) patients, neurological in 3 (20%) and previous infection in 3 (20%). Mean laboratorial values were: Hemoglobin 7.8 g/dL, platelets 161.000/uL; LDH 586 UL; bilirubin 1.38 mg/dL, haptoglobin 1, 55 g/L. Only 5 had schistocytes. ADAMTS13 activity was >10% in all performed and in all, Coombs test were negative. C3 was consumed in 3 (20%) patients and C4 in 2 (13%) but complement phenotypic study was normal in all performed patients. Auto-immune study revealed: 1 positive ANA, dsDNA negative in all but one with positive c1q antibody. One had positive antiphospholipid syndrome (AFS) antibodies and one scleroderma antibodies. Main kidney presentation was acute kidney injury in 8 (53%) patients, with mean eGFR 14ml/min/1, 73m2. Mean proteinuria was 2, 5 g/24h and half (50%) had hematuria. Kidney biopsies had a mean of 11, 85 glomerulus, of which 14% sclerotic, mean interstitial fibrosis and tubular atrophy score 1, 7. Acute tubular necrosis was present in 7 (46%) and inflammatory infiltrate in all, endotheliosis in 13 (86%), mesangiolysis in 3 (20%), arteriolar thrombus in 10 (66%), glomerular thrombus in 6 (40%), ischemic glomerulus in 12 (80%) and double-contour appearance in 7 (46%). TMA etiologies were the following: 2 malignant hypertension, 2 proteasome inhibitor (PI), 1 scleroderma, 1 lupus, 1 AFS, 2 calcineurin and mammalian target of rapamycin inhibitors, 2 antibody mediated rejection (AMR), 1 methylmalonic acidemia and 2 undetermined. Treatment performed encompassed: hypertension management, withdrawal od PI, changing immunosuppression, AMR treatment, cyanocobalamin, lupus induction treatment and eculizumab. Kidney recovery was observed in 8 patients (53%). Patient survival at 6 months was 73%. Conclusion: These study results highlight the vast context of conditions that TMA can appear. Most of them had only with mild or even absent clinical and laboratory features. Therefore, a high index of suspicion is required to diagnose TMA, allowing targeted treatment to preserve of kidney function.